Development of Fibrotic Processes in the Liver under Conditions of Long-Term Immunosuppressive Therapy and its Immunohistochemical Prognostic Indicators - G’ulom qizi, Jurayeva Barno; M. Z., Sanakulova (American Journal of Bioscience and Clinical Integrity, 2026)
Chronic immunosuppressive therapy, widely used in organ transplantation and autoimmune disorders, is associated with the development of liver fibrosis, a progressive condition that may culminate in cirrhosis and liver failure. Fibrogenesis is driven by persistent hepatocellular injury, activation of hepatic stellate cells, extracellular matrix accumulation, and dysregulation of inflammatory and profibrotic signaling pathways. Immunohistochemical markers, including α-smooth muscle actin (α-SMA), transforming growth factor-beta (TGF-β), and collagen type I, provide valuable prognostic information on the stage and progression of fibrosis. This article comprehensively analyzes the molecular and cellular mechanisms underlying liver fibrosis in patients receiving long-term immunosuppressants, evaluates immunohistochemical prognostic indicators, and discusses implications for monitoring, early detection, and potential therapeutic interventions to mitigate hepatic damage. Understanding these mechanisms is essential for improving long-term outcomes in patients under chronic immunosuppressive regimens. Long-term immunosuppressive therapy, a cornerstone in organ transplantation and the management of autoimmune disorders, is closely associated with the development of progressive liver fibrosis, which may ultimately result in cirrhosis and compromised hepatic function. The pathogenesis of fibrosis involves sustained hepatocyte injury, chronic inflammatory responses, activation of hepatic stellate cells, and excessive deposition of extracellular matrix components, particularly collagen. Immunohistochemical evaluation using markers such as α-smooth muscle actin (α-SMA), transforming growth factor-beta (TGF-β), and collagen type I enables precise assessment of fibrotic activity and prognostic stratification. This article provides a detailed review of the molecular and cellular mechanisms underlying fibrogenesis in the context of prolonged immunosuppressive therapy and highlights the utility of immunohistochemical indicators in predicting disease progression. Understanding these processes is essential for optimizing patient management, guiding therapeutic adjustments, and mitigating the long-term hepatic complications associated with chronic immunosuppressive treatment.